(untitled) (Medico Legal Update, 2020)
Early identification of Proteinuria by using urine dipstick among patients with Type II Diabetes in Selected Community Area, Kanchipuram Dist, Tamil Nadu, India. The objectives of the study to assess the Proteinuria by using urine dipstick among Patients with Type II Diabetes. To find out the association between level of Proteinuria with selected demographic variables among Patients with Type II Diabetes.. The sampling technique was non probability- purposive sample technique and the sample size was 200. The demographic variable proforma and the random urine dipstick analysis were done to identify the prevalence of proteinuria. The interpretations were nil, trace, 1+, 2+ and 3+.. Hypothesis were formulated. The level of significance selected was p<0.05. The data was collected and it was analyzed by descriptive and inferential statistics. It presented through tables and figures. The study finding revealed that (47%) of patients were not having proteinuria. Then (38.5%) were having trace, (12%) of patients having 1+, (1.5%) having 2+ and (1%) patients were having 3+ of proteinuria. The study finds also revealed that there was a significant association between the demographic variables such as age X2=8.4120,educational status X2=6.8901, monthly income X2=10.9762, occupational status X2=4.9031, history of diabetes X2=12.14, previous blood glucose level X2=0.9876, family history X2=5.1056, unhealthy habits X2=10.74 were non significant to p<0.05 were as,marital status X2=16.428, dietary pattern X2=17.594 were significant to p>0.05 with the level of prevalence of proteinuria among type II diabetes patients.